2022
DOI: 10.1002/chem.202202237
|View full text |Cite
|
Sign up to set email alerts
|

Well‐Defined Ni(0) and Ni(II) Complexes of Bicyclic (Alkyl)(Amino)Carbene (MeBICAAC): Catalytic Activity and Mechanistic Insights in Negishi Cross‐Coupling Reaction

Abstract: Negishi cross‐coupling reaction of organozinc compounds as nucleophiles with aryl halides has drawn immense focus for C−C bond formation reactions. In comparison to the well‐established library of Pd complexes, the C−C cross‐coupling of this particular approach is largely primitive with nickel‐complexes. Herein, we describe the syntheses of Ni(II) complexes, [(MeBICAAC)2NiX2] (X=Cl (1), Br (2), and I (3)) by employing the bicyclic (alkyl)(amino)carbene (MeBICAAC) ligand. The reduction of complexes 1–3 using KC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Ni–C 1.91(2) Å and Ni–Br 2.32(2) Å, 50 structures) 42 and trans -(Me 2 CAAC) 2 NiX 2 (X = Cl, Br, I; av. Ni–C 1.935(5) Å and Ni–Br 2.300(8) Å, 4 structures) 43 , 44 . As 3 induces a relatively weak-field splitting in the pseudotetrahedral coordination geometry it imposes 45 , it allows for an interesting high-spin configuration in the case of 4 , in agreement with theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ni–C 1.91(2) Å and Ni–Br 2.32(2) Å, 50 structures) 42 and trans -(Me 2 CAAC) 2 NiX 2 (X = Cl, Br, I; av. Ni–C 1.935(5) Å and Ni–Br 2.300(8) Å, 4 structures) 43 , 44 . As 3 induces a relatively weak-field splitting in the pseudotetrahedral coordination geometry it imposes 45 , it allows for an interesting high-spin configuration in the case of 4 , in agreement with theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%
“…Crystallographic characterization revealed that the isocrystalline complexes 4-7 feature a pseudotetrahedral coordination environment at the metal (τ 4 ' = 0.96-1.01) with a chelating ligand 3 (Fig. 4) 41 43,44 . As 3 induces a relatively weak-field splitting in the pseudotetrahedral coordination geometry it imposes 45 , it allows for an interesting high-spin configuration in the case of 4, in agreement with theoretical calculations.…”
Section: Resultsmentioning
confidence: 99%